HUBUNGAN PERILAKU PENCEGAHAN COVID-19 DENGAN TINGKAT STRES PADA MAHASISWA KEPANITERAAN KLINIK PROFESI DOKTER FAKULTAS KEDOKTERANUNIVERSITAS ANDALAS - Erika, Niken Ayu Putri; Yaunin, Yaslinda; Isrona, Laila; Yulistini, Yulistini; Ashal, Taufik; Almurdi, Almurdi (SINERGI : Jurnal Riset Ilmiah, 2025)
The COVID-19 pandemic has affected the clinical learning environment of medical students, who are required to have knowledge, attitudes, and take actions to control COVID-19 infection. The pandemic can be one of the stressors for students undergoing clinical clerkships. Incorrect knowledge, attitudes, and actions can result in infection transmission and cause an increase in stress. The aim of this study was to determine the relationship between knowledge, attitudes, and preventive actions of COVID-19 with the level of stress among medical students undergoing clinical clerkships at the Faculty of Medicine, Andalas University. This study was an analytical research with a cross-sectional approach. The research sample consisted of 246 individuals obtained using cluster random sampling techniques. The research data were in the form of primary data obtained through filling out questionnaires regarding knowledge, attitudes, and preventive actions of COVID-19, and DASS-42. Data analysis used the Spearman rank test with statistical significance determined if p-value < 0.05. Bivariate analysis showed a significant relationship between knowledge, attitudes, and actions with the level of stress with the value of knowledge (p = 0.008, r = -0.168), attitudes (p = 0.045, r = -0.128), and actions (p = 0.011, r = -0.162). The conclusion of this study is that there is a significant relationship, a negative relationship pattern, and a very weak strength of the relationship between knowledge, attitudes, and preventive actions of COVID-19 with the level of stress among medical students undergoing clinical clerkships at the Faculty of Medicine, Andalas University